2016
DOI: 10.1063/1.4955030
|View full text |Cite
|
Sign up to set email alerts
|

All electrical propagating spin wave spectroscopy with broadband wavevector capability

Abstract: We develop an all electrical experiment to perform the broadband phase-resolved spectroscopy of propagating spin waves in micrometer sized thin magnetic stripes. The magnetostatic surface spin waves are excited and detected by scaled down to 125 nm wide inductive antennas, which award ultra broadband wavevector capability. The wavevector selection can be done by applying an excitation frequency above the ferromagnetic resonance. Wavevector demultiplexing is done at the spin wave detector thanks to the rotation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 22 publications
1
83
1
Order By: Relevance
“…In practice, however, unidirectional spin-wave propagation is not necessarily restricted to this narrow frequency range. Indeed, the normal modes closest in frequency to the gap have profiles such that they hardly couple to laterally homogeneous excitations produced by magnetic field line sources, as those assumed for our numerical simulations, or coplanar waveguide inductive antenna, as most often employed in experiments [27,28]. As a result, the effectively useful frequency window can be much wider, reaching nearly half a GHz in the present case [ Fig.…”
mentioning
confidence: 76%
“…In practice, however, unidirectional spin-wave propagation is not necessarily restricted to this narrow frequency range. Indeed, the normal modes closest in frequency to the gap have profiles such that they hardly couple to laterally homogeneous excitations produced by magnetic field line sources, as those assumed for our numerical simulations, or coplanar waveguide inductive antenna, as most often employed in experiments [27,28]. As a result, the effectively useful frequency window can be much wider, reaching nearly half a GHz in the present case [ Fig.…”
mentioning
confidence: 76%
“…Single wire antennas have been conventionally used for the study of spin-waves 26 . The inductive fields generated by single wire antenna decay inversely with the distance, and hence, could lead to a strong inductive coupling between the transmitting and receiving antenna.…”
Section: -D Model For Sw Propagationmentioning
confidence: 99%
“…The transmission signal of BVSW was found experimentally to be small and comparable to the electromagnetic crosstalk between the two antennas. To better reveal the spin wave signal in the BVSW configuration, the magnetic field derivative of the measured frequency response is used to retain only the SW signal 26 . A low RF power of -10 dBm was used for the measurements.…”
Section: -D Model For Sw Propagationmentioning
confidence: 99%
“…It is shown that a critical waveguide width exists, below which the profiles of the spin-wave modes are essentially uniform across the width of the waveguide. This is fundamentally different from the profiles in state-of-the-art waveguides of micrometer [16][17][18][19] or millimeter sizes [25,26], where the profiles are non-uniform and pinned at the waveguide edges due to the dipolar interaction. In nanoscopic waveguides, the exchange interaction suppresses this pinning due to its dominance over the dipolar interaction and, consequently, the exchange interaction defines the profiles of the spin-wave modes as well as the corresponding spin-wave dispersion characteristics.…”
mentioning
confidence: 90%